Transformation of primary care during the COVID-19 pandemic: experiences of healthcare professionals in eight European countries - Wanat, Marta; Hoste, Melanie; Gobat, Nina; Anastasaki, Marilena; Böhmer, Femke; Chlabicz, Slawomir; Colliers, Annelies; Farrell, Karen; Karkana, Maria-Nefeli; Kinsman, John; Lionis, Christos; Marcinowicz, Ludmila; et al. (British journal of general practice, 2021)
Primary care has a crucial role in responding to the COVID-19 pandemic as the first point of patient care and gatekeeper to secondary care. Qualitative studies exploring the experiences of healthcare professionals during the COVID-19 pandemic have mainly focused on secondary care. To gain an understanding of the experiences of European primary care professionals (PCPs) working during the first peak of the COVID-19 pandemic. An exploratory qualitative study, using semi-structured interviews in primary care in England, Belgium, the Netherlands, Ireland, Germany, Poland, Greece, and Sweden, between April and July 2020. Interviews were audiorecorded, transcribed, and analysed using a combination of inductive and deductive thematic analysis techniques. Eighty interviews were conducted with PCPs. PCPs had to make their own decisions on how to rapidly transform services in relation to COVID-19 and non-COVID-19 care. Despite being overwhelmed with guidance, they often lacked access to practical training. Consequently, PCPs turned to their colleagues for moral support and information to try to quickly adjust to new ways of working, including remote care, and to deal with uncertainty. PCPs rapidly transformed primary care delivery despite a number of challenges. Representation of primary care at policy level and engagement with local primary care champions are needed to facilitate easy and coordinated access to practical information on how to adapt services, ongoing training, and access to appropriate mental health support services for PCPs. Preservation of autonomy and responsiveness of primary care are critical to preserve the ability for rapid transformation in any future crisis of care delivery.